„Moderní apoštolát našich zásad“. Ženský tisk Československé strany lidové v Čechách v předvolebním období 1919 a 1920 - Marie V. Fousková (Gender a Výzkum, 2016)
The municipal elections of 1919 and the parliamentary/senate elections of 1920 gave women their first opportunity to exercise their new right to vote, and as such were important milestones in the forming of women’s new status as equal citizens. The paper analyses election campaigns aimed at female voters in selected periodicals published by the Czech Catholic People’s Party in 1919 and 1920: the newspaper Lid (The People) and the newly established magazine Žena (Woman). It explores the main topics and strategies of the campaign and identifies the underlying concepts of women’s political interests and motivations. The main focus is on the magazine Žena and its attempts to reconcile traditional Catholic femininity and the ‘separate spheres’ model with women’s newfound status as political actors and to create a picture of a new, politically active Catholic woman for its readership.